Correction to: Healthcare professionals' perspectives on working conditions, leadership, and safety climate: a cross-sectional study - Anke Wagner; Monika A. Rieger; Tanja Manser; Heidrun Sturm; Juliane Hardt; Peter Martus; Constanze Lessing; Antje Hammer; on behalf of the WorkSafeMed Consortium (BMC, 2020)
In the original publication of this article [1], the authors missed that reverse coding was necessary for the item "Do you work separate from your colleagues?" before calculating the scale 'social relations'. So they corrected the analysis accordingly. The results with the revised scale show that there are no longer any significant differences between nurses and physicians with regard to this scale.